Penanganan Kekerasan Terhadap Perempuan di Denmark di bawah Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) dibalik Tingginya Prevalensi Kekerasan Terhadap Perempuan pada tahun 2014 - Amanda Alya Sarrah; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
Violence against women is a form of discrimination against women and is regulated under the 1981 Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW). Violence against women is a global issue. It also still occurs in developed countries such as Denmark. In fact, despite the remarkable achievements in the agenda of gender equality in the economic, political and social fields, the prevalence of violence that occurred in 2003 and 2014 was still high. As a binding instrument, CEDAW provides an obligation for the state to comply with and to implement concrete measures in the protection of women. Therefore, the author in this study sought to see how Denmark's compliance forms to fulfill its obligations in dealing with violence against women according to this Convention. This qualitative research uses compliance theory by paying attention to the dynamics and the challenges of handling violence against women under the Convention. There are several findings in this study. First, although Denmark has implemented significant measures in dealing with violence against women, CEDAW has not been fully implemented by Denmark. Second, the increasing number of immigrants and the financial crisis have affected the success in protecting women. Third, the social and cultural conditions of the community have not completely changed. Therefore, Denmark can be categorized as a high compliance-low effectiveness country.